The influence of rain intensity on raindrop diameter and the kinetics of tropical rainfall: case study of Skudai, Malaysia - Yakubu, Mahadi Lawan (Taylor and Francis Ltd., 2016)
The modelling of soil loss and investigation of urban hydrology and wet weather pollution in Malaysia requires the definition of rainfall parameters for the region. In this study, an inexpensive method was applied to establish the influence of raindrop diameter on kinetics and rain intensity in Skudai, Peninsular Malaysia, as a prelude to wider regional research. Raindrop sizes vary from less than 1.2Â mm to as big as 7.0Â mm, with median raindrop diameters of 2.51Â mm and a mean diameter of 2.56Â mm. The median raindrop diameter–intensity relationship correlates strongly using power and exponential equations, with coefficients of determination of 0.75 and 0.73, respectively. The kinetic energy–intensity relationship fits an exponential function and also a linear equation with R2Â values ofÂ 0.49 and 0.34, respectively. An average rain kinetic energy of 30Â JÂ m-2Â mm-1 was recorded. This research leads to an objective reclassification of rainfall intensities in the region. Editor Z.W. Kundzewicz; Associate editor not assigned Â